Poor efficacy and tolerability of R‐CHOP in relapsed/refractory chronic lymphocytic leukemia and Richter transformation. Issue 12 (26th September 2014) - Langerbeins, Petra; Busch, Raymonde; Anheier, Nadine; Dürig, Jan; Bergmann, Manuela; Goebeler, Maria‐Elisabeth; Hurtz, Hans‐Jürgen; Stauch, Martina B.; Stilgenbauer, Stephan; Döhner, Hartmut; Fink, Anna‐Maria; Cramer, Paula; et al.
<x xml:space="preserve">Abstract</x> This phase II trial evaluated efficacy and tolerability of R‐CHOP for up to 8 courses in Richter transformation (RT) and up to 6 courses in CLL plus autoimmune cytopenia (AIC) or high‐risk (HR) features. HR was defined as fludarabine‐refractoriness or early relapse (<36 months) after fludarabine‐based treatment; 26 patients were included as HR, 19 patients had AIC, and 15 patients had RT. In the HR cohort, overall response rate was 54%, progression‐free and overall survival were 9 and 21 months. In AIC patients overall response rate was 74%, progression‐free and overall‐survival were 10 and 41 months, respectively, and median increase in hemoglobin was 3.4 g/L. RT patients responded in 67%, progression‐free was 10 and overall survival 21 months. The most common adverse events were hematologic toxicities in 92%. Severe infections occurred in 28%. Treatment was discontinued early in 45% of all patients mainly as a result of toxicity. This trial shows that R‐CHOP has no role in treating complicated CLL. R‐CHOP is associated with significant toxicities and fairly low efficacy compared with almost every other CLL‐regimen. In RT, it might still be used as an induction therapy before allogeneic stem cell transplantation. Am. J. Hematol. 89:E239–E243, 2014. © 2014 Wiley Periodicals, Inc.